Correction of Financial Disclosure (Annals of Medical Research, 2019)
Videolaryngoscopy versus direct laryngoscopy in without muscle relaxation intubation conditions intympanomastoidectomy: A randomized, prospective clinical study” titled study (2019; 26 (2): 246-9, DOI: 10.5455/annalsmedres.2018.09.184) has been supported by Inonu University Department of Scientific Research Projects(Project number: 2016/85).